1998
DOI: 10.1017/s003329179700648x
|View full text |Cite
|
Sign up to set email alerts
|

Theory of mind and psychoses

Abstract: Impaired theory of mind on second order tests is specific to schizophrenia when compared to mild learning disability and affective disorder control groups. Subjects with schizophrenia and pre-morbid mild learning disability show greater impairment than subjects with schizophrenia and a pre-morbid IQ within the normal range.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
106
1
15

Year Published

1999
1999
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 253 publications
(128 citation statements)
references
References 38 publications
6
106
1
15
Order By: Relevance
“…Doody et al (1998) found that the schizophrenics' deficit in second-order ToM did not correlate with their IQ, while Pickup and Frith (2001) found a ToM impairment only in a second-order task and it was associated with low IQ. Brüne (2003) found a correlation between the verbal IQ of schizophrenic subjects and their performance at ToM tasks; the correlation still existed when the IQ of the subjects and of the controls was matched.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Doody et al (1998) found that the schizophrenics' deficit in second-order ToM did not correlate with their IQ, while Pickup and Frith (2001) found a ToM impairment only in a second-order task and it was associated with low IQ. Brüne (2003) found a correlation between the verbal IQ of schizophrenic subjects and their performance at ToM tasks; the correlation still existed when the IQ of the subjects and of the controls was matched.…”
Section: Discussionmentioning
confidence: 95%
“…A large body of empirical evidence appears to support Frith's hypothesis: schizophrenic subjects perform worse than normal at several types of ToM tasks (Corcoran, Mercer, & Frith, 1995;Doody, Götz, Johnstone, Frith, & Cunningham Owens, 1998;Frith & Corcoran, 1996;Mazza, De Risio, Surian, Roncone, & Casacchia, 2001;Mazza, De Risio, Tozzini, Roncone, & mental states, both of her own and of the others. Beside what has been discussed in the previous section, another major reason why Th.o.m.a.s.…”
Section: Introductionmentioning
confidence: 92%
“…So far, little is known about social cognition in major depression on more complex socially relevant tasks, such as false-belief or humor processing tasks. Doody et al (1998) administered false belief tasks to patients with schizo-phrenia, learning disability, and affective disorders. Those who were depressed showed generally intact performance on false belief tasks.…”
Section: Introductionmentioning
confidence: 99%
“…Corcoran 2003;Corcoran & Frith, 2003;Frith, 2004), even at a first episode of psychosis (Bertrand, et al, 2007). There is also a growing body of research into ToM performance in affective disorders (Bonshtein et al, 2006;Bora et al, 2005;Bora et al, 2009;Corcoran et al 2008;Doody et al, 1998;Kerr et al, 2003;Inoue et al, 2006;Lahera et al, 2008;Malhi et al, 2008;Montag et al 2010;Schenkel et al, 2008).…”
Section: Adults With Grandiose Delusionsmentioning
confidence: 99%